Durasphere® EXP: a non-biodegradable agent for treatment of primary Vesico-Ureteral reflux in children - Unsal Ozkuvanci (International Brazilian Journal of Urology)
ABSTRACT Introduction: Durasphere® EXP (DEXP) is a compound of biocompatible and non--biodegradable particles of zirconium oxide covered with pyrolytic carbon. The aim of this study is to evaluate the durability of off-label use of DEXP in the treatment of primary vesicoureteral reflux in children. Materials and Methods: Patients who underwent subureteric injection of DEXP for the correction of primary VUR were retrospectively reviewed. Patients aged >18 years as well as those who had grade-I or -V VUR, anatomic abnormalities (duplicated system, hutch diverticulum), neurogenic bladder or treatment refractory voiding dysfunction were excluded. Radiologic success was defined as the resolution of VUR at the 3rd month control. Success was radiographically evaluated at the end of the first year. Results: Thirty-eight patients (9 boys, 29 girls; mean age, 6.3±2.7 years) formed the study cohort. Forty-six renal units received DEXP (grade II: 22; grade III: 18; grade IV: 6). Mean volume per ureteric orifice to obtain the mound was 0.70±0.16mL. First con- trol VCUG was done after 3 months in all patients. After the first VCUG, 6 patients had VUR recurrence. Short-term radiologic success of DEXP was 84.2%. Rate of radiologic success at the end of the first year was 69.4% (25/32). Lower age (p:0.006) and lower amount of injected material (p:0.05) were associated with higher success rates at the end of 1 year. Conclusion: This is the first study to assess the outcomes of DEXP for treatment of primary VUR in children. After 1 year of follow-up, DEXP had a 69.4% success rate.